Chloroprene copolymer latex composition and molded product thereof
The chloroprene copolymer latex composition, utilizing chloroprene and 2-methyl-1,3-butadiene with specific vulcanization accelerators, addresses the flexibility and strength imbalance in chloroprene rubber, producing high-quality medical gloves without harmful additives.
Patent Information
- Application Number
- JP2021567610
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-24
- Filing Date
- 2020-12-24
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2040-12-24
AI Technical Summary
Chloroprene rubber products face challenges in achieving a balance between flexibility and tensile strength, and they often contain sensitizing substances like diphenylguanidine or N,N'-diphenylthiourea, which are restricted in Europe.
A chloroprene copolymer latex composition using a chloroprene copolymer containing monomer units from chloroprene and 2-methyl-1,3-butadiene, combined with thiazole-based and carbamate-based vulcanization accelerators, along with optional metal oxide, sulfur, and antioxidant, to enhance flexibility and tensile strength without using diphenylguanidine or N,N'-diphenylthiourea.
The composition allows for the production of molded articles with high flexibility and tensile strength, suitable for medical disposable gloves, while avoiding sensitizing substances, thus ensuring safety and effectiveness.
Smart Images

Figure 0007616075000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a latex composition containing as a main component a copolymer of 2-chloro-1,3-butadiene (chloroprene) and 2-methyl-1,3-butadiene, and to a molded product, particularly a dipped product, using the composition. [Background technology]
[0002] Isoprene rubber (IR) and chloroprene rubber (CR) are synthetic rubbers that have the same flexibility as natural rubber. For this reason, in recent years, isoprene rubber or chloroprene rubber has been used instead of natural rubber in dip molding composition products (dipped products), especially surgical gloves, as a countermeasure against allergies. Since isoprene rubber is highly flexible and easily follows the movements of the hand, gloves made from isoprene rubber tend to provide a good feel (touch) for medical workers, but isoprene rubber is expensive and does not fully meet market demands. On the other hand, chloroprene rubber can be produced more cheaply than isoprene rubber, but there are issues such as its inferior flexibility and the reduction in tensile strength when trying to give flexibility to chloroprene rubber.
[0003] For example, with regard to chloroprene rubber, Patent Document 1 discloses a technology for improving flexibility, but the tensile strength is reduced. For example, Patent Document 2 discloses a technology for exhibiting high strength through a manufacturing method or vulcanization compounding, but the flexibility is reduced and the rubber does not sufficiently combine flexibility and high strength. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2019-143002 A [Patent Document 2] JP 2019-044116 A Summary of the Invention [Problem to be solved by the invention]
[0005] The present invention aims to solve the above-mentioned problems of the conventional techniques and to provide a chloroprene copolymer latex that can give molded products having excellent flexibility at a low cost. Another aim of the present invention is to provide a chloroprene copolymer latex composition without using diphenylguanidine or N,N'-diphenylthiourea, which are becoming recognized as sensitizing substances in Europe. [Means for solving the problem]
[0006] As a result of intensive research into solving the above problems, the present inventors have found that the above problems can be solved by using a latex of a chloroprene copolymer (A) containing a monomer unit derived from chloroprene and a monomer unit derived from 2-methyl-1,3-butadiene, and by using a thiazole-based vulcanization accelerator and a carbamate-based vulcanization accelerator as vulcanization accelerators, and have completed the present invention. That is, the present invention relates to the following chloroprene copolymer latex composition, and a molded article and a dipped product obtained by curing the composition.
[0007] [1] A chloroprene copolymer latex composition comprising a chloroprene copolymer (A) and a vulcanization accelerator (B), The chloroprene copolymer (A) is a chloroprene copolymer containing chloroprene and a monomer unit derived from 2-methyl-1,3-butadiene, The chloroprene copolymer latex composition, wherein the vulcanization accelerator (B) contains a carbamate-based vulcanization accelerator and a thiazole-based vulcanization accelerator.
[0008] [2] The chloroprene copolymer latex composition according to [1], wherein the thiazole vulcanization accelerator is 2-mercaptobenzothiazole zinc.
[0009] [3] The carbamate-based vulcanization accelerator is diethyldithiocarbamate. AcidThe chloroprene copolymer latex composition according to [1] or [2], wherein the additive is at least one selected from the group consisting of lead, zinc dibutyldithiocarbamate, and sodium dibutyldithiocarbamate.
[0010] [4] The chloroprene copolymer latex composition according to any one of [1] to [3], further comprising a metal oxide (C), sulfur (D), and an antioxidant (E).
[0011] [5] 100 parts by mass in total of the chloroprene copolymer (A) and the optional synthetic rubber (F), 1.0 to 10.0 parts by mass of a vulcanization accelerator (B), 0.1 to 20.0 parts by mass of a metal oxide (C), Sulfur (D) 0.1 to 10.0 parts by mass, and 0.1 to 10.0 parts by mass of antioxidant (E) The chloroprene copolymer latex composition according to [4],
[0012] [6] Contains synthetic rubber (F), The chloroprene copolymer latex composition according to [5], wherein the proportion of the synthetic rubber (F) is 1 to 33 mass% when the total of the chloroprene copolymer (A) and the synthetic rubber (F) is 100 mass%.
[0013] [7] A chloroprene copolymer rubber molded product obtained by curing the chloroprene copolymer latex composition according to any one of [1] to [6].
[0014] [8] A dipping product obtained by molding the chloroprene copolymer latex composition according to any one of [1] to [6] by a dipping method and curing it. [9] The dipped product according to [8], which is a glove.
[10] The dipped product described in [9], which is a disposable medical glove.
[0015]
[11] An dipped product according to any one of [8] to
[10] , wherein the surface of the dipped product is free of powder that reduces friction between the dipped product and an object with which the dipped product comes into contact.
[12] A multilayer dipping product having a multilayer structure in which a layer obtained by molding and curing the chloroprene copolymer latex composition according to any one of [1] to [6] is laminated with a layer other than the above layer. Effect of the Invention
[0016] By vulcanizing the chloroprene copolymer latex composition of the present invention, a molded product (chloroprene copolymer rubber molded product) having high flexibility and high tensile strength can be obtained. In addition, since the chloroprene copolymer latex composition of the present invention does not contain a vulcanization accelerator which may cause skin sensitization, the molded product produced from the chloroprene copolymer latex composition of the present invention can be suitably used for dipping products, particularly disposable medical gloves. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] Hereinafter, the embodiments of the present invention will be described in detail, but the present invention is not limited to the configurations of the following embodiments. In the claims and the description of this specification, the term "to" specifying a numerical range means a value equal to or greater than the lower limit and equal to or less than the upper limit.
[0018] <Chloroprene copolymer latex composition> The chloroprene copolymer latex composition of the present invention contains a chloroprene copolymer (A) and a vulcanization accelerator (B). Hereinafter, a case where the chloroprene copolymer latex composition is produced by mixing a latex of the chloroprene copolymer (A) and the vulcanization accelerator (B) will be described as an example.
[0019] <Latex of chloroprene copolymer (A)> In the latex of the chloroprene copolymer (A), fine particles of the chloroprene copolymer (A) are dispersed in a dispersion medium such as water.
[0020] [Chloroprene copolymer (A)] The chloroprene copolymer (A) contains at least a structure (monomer unit) derived from 2-chloro-1,3-butadiene (chloroprene) (A-1) and a structure (monomer unit) derived from 2-methyl-1,3-butadiene (A-2). The monomers constituting the chloroprene copolymer (A) may be only 2-chloro-1,3-butadiene (A-1) and 2-methyl-1,3-butadiene (A-2).
[0021] When all monomer units constituting the chloroprene copolymer (A) are taken as 100 mol %, the proportion of monomer units derived from 2-chloro-1,3-butadiene (A-1) is preferably 70 to 90 mol %, more preferably 73 to 90 mol %, even more preferably 75 to 89 mol %, and particularly preferably 84 to 89 mol %. If the ratio of the monomer units derived from 2-chloro-1,3-butadiene (A-1) in the chloroprene copolymer (A) is 73 mol% or more, the polymerization reaction tends to proceed quickly, which is preferable. If the ratio of the monomer units derived from 2-chloro-1,3-butadiene (A-1) in the chloroprene copolymer (A) is 90 mol% or less, the molded product obtained by vulcanizing the chloroprene copolymer latex composition has high flexibility, which is preferable.
[0022] When the total monomer units constituting the chloroprene copolymer (A) is taken as 100 mol %, the proportion of 2-methyl-1,3-butadiene (A-2) is preferably 10 to 30 mol %, more preferably 10 to 27 mol %, further preferably 11 to 25 mol %, and particularly preferably 11 to 16 mol %. The proportion of 2-methyl-1,3-butadiene (A-2) is preferably 10 to 30 mol %, more preferably 10 to 27 mol %, further preferably 11 to 25 mol %, and particularly preferably 11 to 16 mol %. 1 Determined by H-NMR analysis. When the ratio of monomer units derived from 2-methyl-1,3-butadiene (A-2) in the chloroprene copolymer (A) is 10 to 30 mol %, the molded product obtained when vulcanized at 110° C. has good tensile strength, which is preferable.
[0023] The chloroprene copolymer (A) may contain a monomer unit derived from a monomer (A-3) in addition to a structure (monomer unit) derived from 2-chloro-1,3-butadiene (A-1) and a structure (monomer unit) derived from 2-methyl-1,3-butadiene (A-2) without impairing the object of the present invention. Here, the monomer (A-3) is a monomer other than 2-chloro-1,3-butadiene (A-1) and 2-methyl-1,3-butadiene (A-2) and is copolymerizable with at least one of 2-chloro-1,3-butadiene (A-1) and 2-methyl-1,3-butadiene (A-2). The monomer (A-3) may be a monomer copolymerizable with both 2-chloro-1,3-butadiene (A-1) and 2-methyl-1,3-butadiene (A-2). Examples of the monomer (A-3) include butadiene, 2,3-dichloro-1,3-butadiene, styrene, acrylonitrile, acrylic acid and its esters, methacrylic acid and its esters, etc. The chloroprene copolymer (A) may contain structures derived from two or more types of monomer (A-3) as necessary.
[0024] The proportion (upper limit) of the monomer (A-3) when the chloroprene copolymer (A) contains a monomer (A-3) unit is preferably 10 mol parts or less, more preferably 8 mol parts or less, and even more preferably 5 mol parts or less, when the total of the monomer units derived from 2-chloro-1,3-butadiene (A-1) and the monomer units derived from 2-methyl-1,3-butadiene (A-2) in the chloroprene copolymer (A) is taken as 100 mol parts. The proportion (lower limit) of the monomer (A-3) when the chloroprene copolymer (A) contains a monomer (A-3) unit is preferably 0.01 mol parts or more, more preferably 0.5 mol parts or more, and even more preferably 1.0 mol parts or more, when the total of the monomer units derived from 2-chloro-1,3-butadiene (A-1) and the monomer units derived from 2-methyl-1,3-butadiene (A-2) in the chloroprene copolymer (A) is taken as 100 mol parts. When the ratio of the monomer (A-3) is 10 parts by mol or less when the total of the monomer units derived from 2-chloro-1,3-butadiene (A-1) and the monomer units derived from 2-methyl-1,3-butadiene (A-2) in the chloroprene copolymer (A) is taken as 100 parts by mol, the molded product has good tensile strength and elongation, and the flexibility of the molded product has good stability over time.
[0025] The chloroprene copolymer (A) has a tetrahydrofuran (THF) insoluble content at 25° C. of preferably 30% by mass or less, more preferably 20% by mass or less, and further preferably 10% by mass or less. If the tetrahydrofuran insoluble content in the chloroprene copolymer (A) is 30% by mass or less, the flexibility and tensile strength of the molded product obtained by vulcanization treatment are good, which is preferable. The tetrahydrofuran insoluble content in the chloroprene copolymer (A) is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, and even more preferably 1.5% by mass or more. If the tetrahydrofuran insoluble content in the chloroprene copolymer (A) is 0.01% by mass or more, crosslinking in the chloroprene copolymer (A) has progressed, which is preferable. The tetrahydrofuran insoluble matter is gelled due to three-dimensional crosslinking of polymer chains in the chloroprene copolymer particles. The tetrahydrofuran insoluble matter ratio can be measured by the method employed in the examples described below.
[0026] The tetrahydrofuran insoluble content in the chloroprene copolymer (A) can be controlled by adjusting the polymerization conversion rate and the amount of the chain transfer agent. The polymerization conversion rate is controlled by the polymerization time and polymerization temperature of the chloroprene copolymer (A). The longer the polymerization time, the higher the polymerization conversion rate tends to be, and the higher the polymerization temperature, the higher the polymerization conversion rate tends to be. For example, the tetrahydrofuran insoluble content in the chloroprene copolymer (A) tends to increase as the polymerization conversion rate increases, and the tetrahydrofuran insoluble content in the chloroprene copolymer (A) tends to decrease as the amount of the chain transfer agent coexisting during emulsion polymerization of the chloroprene copolymer (A) increases.
[0027] The weight average molecular weight of the component in the chloroprene copolymer (A) that is soluble in tetrahydrofuran at 25° C., measured by the method or conditions employed in the examples described below, is preferably 400,000 or more, more preferably 500,000 or more, and even more preferably 550,000 or more. If the weight average molecular weight of the component in the chloroprene copolymer (A) that is soluble in tetrahydrofuran at 25° C. is 400,000 or more, a molded product having good mechanical properties can be obtained. The weight average molecular weight of the component in the chloroprene copolymer (A) that is soluble in tetrahydrofuran at 25° C. is preferably 3 million or less, more preferably 2 million or less, and even more preferably 900,000 or less. If the weight average molecular weight of the component in the chloroprene copolymer (A) that is soluble in tetrahydrofuran at 25° C. is 3 million or less, the tetrahydrofuran insoluble content rate is within the desired range, and a molded product having good flexibility and tensile strength can be obtained.
[0028] [Method for producing latex of chloroprene copolymer (A)] As a method for producing a latex of the chloroprene copolymer (A), a method of radically polymerizing 2-chloro-1,3-butadiene (A-1) and 2-methyl-1,3-butadiene (A-2) in an aqueous emulsion is a simple and industrially advantageous method.
[0029] By emulsion-polymerizing 2-chloro-1,3-butadiene (A-1) and 2-methyl-1,3-butadiene (A-2), or 2-chloro-1,3-butadiene (A-1), 2-methyl-1,3-butadiene (A-2), and monomer (A-3) using an emulsifier, a latex in which particles of chloroprene copolymer (A) are dispersed in a dispersion medium such as water is obtained. The polymerization temperature during emulsion polymerization is preferably 20 to 35°C, and the polymerization time is preferably 5 to 8 hours. If the polymerization temperature and polymerization time during emulsion polymerization are within the above ranges, it is preferable because the desired polymerization conversion rate is obtained.
[0030] The 2-methyl-1,3-butadiene content in the chloroprene copolymer (A) can be adjusted by the charging ratio of 2-chloro-1,3-butadiene (A-1) and 2-methyl-1,3-butadiene (A-2) at the time of polymerization charging, the polymerization conversion rate, and the like.
[0031] The higher the ratio of 2-methyl-1,3-butadiene (A-2) in the total monomers at the time of polymerization charging, the higher the content of monomer units derived from 2-methyl-1,3-butadiene (A-2) in the final chloroprene copolymer (A). However, since 2-methyl-1,3-butadiene (A-2) has a lower reactivity at the start of emulsion polymerization compared to 2-chloro-1,3-butadiene (A-1), a high charging ratio of 2-methyl-1,3-butadiene (A-2) tends to slow down the progress of polymerization and lengthen the reaction time.
[0032] Since 2-methyl-1,3-butadiene (A-2) is easily incorporated into the polymer as the polymerization of the chloroprene copolymer (A) proceeds, the content of monomer units derived from 2-methyl-1,3-butadiene (A-2) in the final chloroprene copolymer (A) can be increased by increasing the polymerization conversion rate when polymerizing the chloroprene copolymer (A). In addition, if the polymerization conversion rate is low, the amount of remaining monomer increases, making it necessary to remove the remaining monomer, which is troublesome, and also reduces the mechanical properties of the molded product.
[0033] From the above, in order to efficiently obtain the chloroprene copolymer (A) of the present invention, the content of 2-methyl-1,3-butadiene (A-2) in the total monomer components used is preferably 2 to 40 mol%, more preferably 10 to 30 mol%, and even more preferably 15 to 25 mol%. The polymerization conversion rate of all monomers is preferably 61 to 90 mass%, more preferably 75 to 87 mass%, and even more preferably 80 to 86 mass%. If the polymerization conversion rate of all monomers is 90 mass% or less, the quality of the chloroprene copolymer (A) obtained by polymerization is good, and the physical properties of the molded product obtained from the latex of the chloroprene copolymer (A) are also good.
[0034] Anionic surfactants are preferred as emulsifiers for emulsion polymerization. Examples of anionic surfactants include rosin acid soap, sodium salt of naphthalenesulfonic acid condensate, sodium salt of dodecylbenzenesulfonic acid, and sodium salt of dodecylsulfuric acid. From the viewpoint of ease of coagulation operation, ordinary rosin acid soap can be used. In particular, from the viewpoint of color stability, sodium salt and / or potassium salt of disproportionated rosin acid can be used, and potassium salt of disproportionated rosin acid is more preferred from the viewpoint of polymerization rate.
[0035] The amount of the emulsifier used is preferably 0.5 to 20.0 parts by mass, more preferably 1.0 to 10.0 parts by mass, and even more preferably 1.5 to 5.0 parts by mass, when the total of all monomers including 2-chloro-1,3-butadiene (A-1), 2-methyl-1,3-butadiene (A-2), and monomer (A-3) is taken as 100 parts by mass. If the amount of the emulsifier used is 0.5 parts by mass or more, emulsification failure is unlikely to occur, and heat generation due to polymerization can be controlled. In addition, if the amount of the emulsifier used is 0.5 parts by mass or more, problems such as the formation of aggregates and poor product appearance do not occur. On the other hand, if the amount of the emulsifier used is 20.0 parts by mass or less, the emulsifier such as rosin acid does not remain in the chloroprene copolymer (A), so that the chloroprene copolymer (A) is unlikely to become sticky. Therefore, when the amount of the emulsifier used is 20.0 parts by mass or less, problems in processability and operability due to adhesion to a mold (former) during molding of the chloroprene copolymer latex composition and adhesion during use of the molded product do not occur, and deterioration in color tone of the molded product does not occur.
[0036] As the polymerization initiator, a normal radical polymerization initiator can be used. In the case of emulsion polymerization, for example, organic or inorganic peroxides such as benzoyl peroxide, potassium persulfate, ammonium persulfate, cumene hydroperoxide, t-butyl hydroperoxide, or azo compounds such as azobisisobutyronitrile are used. The polymerization initiator may be used alone or in combination of two or more kinds.
[0037] In the polymerization of the chloroprene copolymer (A) of this embodiment, it is preferable to use a chain transfer agent to adjust the amount of tetrahydrofuran insoluble matter. The amount of the chain transfer agent is preferably 0.01 to 15.0 parts by mass, more preferably 0.05 to 10.0 parts by mass, and even more preferably 0.1 to 1.0 parts by mass, when the total amount of all monomers including 2-chloro-1,3-butadiene (A-1), 2-methyl-1,3-butadiene (A-2) and monomer (A-3) is 100 parts by mass. The chain transfer agent is not particularly limited, but known chain transfer agents such as alkyl mercaptans such as n-dodecyl mercaptan, n-decyl mercaptan, octyl mercaptan, or tert-dodecyl mercaptan, dialkyl xanthogen disulfides such as diisopropyl xanthogen disulfide or diethyl xanthogen disulfide, or iodoform can be used. Alkyl mercaptans are more preferred, and n-dodecyl mercaptan is even more preferred. When the polymerization conversion rate is set to 60 to 90% by mass and the amount of the chain transfer agent used is set to 0.01 to 15.0 parts by mass, the tetrahydrofuran insoluble content in the chloroprene copolymer (A) can be adjusted to a desired range (30% by mass or less).
[0038] In the polymerization of the chloroprene copolymer (A), a cocatalyst may be used together with the polymerization initiator, if desired. The cocatalyst that can be used together with the polymerization initiator is not particularly limited, and a general cocatalyst may be used. For example, anthraquinone sulfonate, potassium sulfite, sodium disulfite, sodium sulfite, tetraethylenepentamine, and N,N-dimethyl-p-toluidine may be used. The cocatalyst may be used alone or in combination of two or more kinds.
[0039] In general, in emulsion polymerization, a polymerization terminator is added at the time when a predetermined polymerization conversion rate is reached in order to obtain a polymer having a desired molecular weight and molecular weight distribution, to terminate the polymerization reaction. A polymerization terminator may also be used in the embodiment of the present invention. The type of polymerization terminator is not particularly limited, and commonly used polymerization terminators such as phenothiazine, para-t-butylcatechol, hydroquinone, hydroquinone monomethyl ether, diethylhydroxylamine, etc. may be used. The polymerization terminator may be used alone or in combination of two or more kinds.
[0040] Furthermore, a stabilizer such as an acid acceptor and / or an antioxidant may be blended into the latex of the chloroprene copolymer (A) within the scope of the invention.
[0041] [Chloroprene copolymer latex composition] The chloroprene copolymer latex composition in one embodiment of the present invention contains a chloroprene copolymer (A), a vulcanization accelerator (B), and, as optional components, a metal oxide (C), sulfur (D), an antioxidant (E), and a synthetic rubber (F). Here, the latex of the chloroprene copolymer (A) and the solid content of the chloroprene copolymer latex composition are components obtained by drying the latex of the chloroprene copolymer (A) or the chloroprene copolymer latex composition by leaving it in an oven at 141°C for 30 minutes, and are components obtained by removing a dispersing medium such as water from the latex. The chloroprene copolymer latex composition may contain a dispersing medium such as water derived from the latex of the chloroprene copolymer (A). When the synthetic rubber (F) described later is not included, the chloroprene copolymer latex composition preferably further contains 1.0 to 10.0 parts by mass of a vulcanization accelerator (B) based on 100 parts by mass of the solid content in the latex of the chloroprene copolymer (A). In addition, in order to efficiently perform vulcanization, the chloroprene copolymer latex composition preferably contains 0.1 to 20.0 parts by mass of a metal oxide (C), 0.1 to 10.0 parts by mass of sulfur (D), and 0.1 to 10.0 parts by mass of an antioxidant (E) based on 100 parts by mass of the solid content in the latex of the chloroprene copolymer (A). By vulcanizing the chloroprene copolymer latex composition blended in this composition, a safe rubber molded product (for example, a film) can be efficiently obtained. Among the raw materials used for blending, components insoluble in water and components that destabilize the colloidal state of the latex of the chloroprene copolymer (A) are added to the latex of the chloroprene copolymer (A) after preparing an aqueous dispersion in advance.
[0042] The vulcanization accelerator (B) includes a thiazole-based vulcanization accelerator and a carbamate-based vulcanization accelerator. Examples of the thiazole-based vulcanization accelerator include 2-mercaptobenzothiazole, di-2-benzothiazolyl disulfide, and zinc 2-mercaptobenzothiazole. Examples of the carbamate-based vulcanization accelerator include dimethyl di bloodZinc octacarbamate, zinc diethyldithiocarbamate, zinc dibutyldithiocarbamate, zinc N-ethyl-N-phenyldithiocarbamate, sodium dibutyldithiocarbamate, N-pentamethylenediamine blood Examples of the vulcanization accelerator include zinc octacarbamate, zinc dibenzyldithiocarbamate, copper dimethyldithiocarbamate, and tellurium diethyldithiocarbamate. In order to perform the vulcanization treatment efficiently, it is preferable to use sodium dibutyldithiocarbamate, zinc diethyldithiocarbamate, or zinc dibutyldithiocarbamate. These vulcanization accelerators may be used in combination of three or more kinds.
[0043] The vulcanization accelerator (B) may be used in combination with other vulcanization accelerators as necessary. The vulcanization accelerator to be used in combination is not particularly limited, and those generally used in the vulcanization treatment of isoprene-based polymer latex or chloroprene-based polymer latex can be used. For example, thiuram-based vulcanization accelerators, thiourea-based vulcanization accelerators, and guanidine-based vulcanization accelerators can be mentioned. Examples of thiuram-based vulcanization accelerators include tetraethylthiuram disulfide and tetrabutylthiuram disulfide. Examples of thiourea-based vulcanization accelerators include ethylenethiourea, diethylthiourea, trimethylthiourea, and N,N'-diphenylthiourea (DPTU). Examples of guanidine-based vulcanization accelerators include diphenylguanidine (DPG) and di-orthotoluylguanidine. These may be used alone or in combination of two or more.
[0044] The amount of the vulcanization accelerator (B) contained in the chloroprene copolymer latex composition according to this embodiment is preferably 1.0 to 10.0 parts by mass, more preferably 1.2 to 5.0 parts by mass, and even more preferably 1.5 to 3.0 parts by mass, when the amount of the solid content of the latex of the chloroprene copolymer (A) obtained by the above polymerization method is taken as 100 parts by mass. If the amount of the vulcanization accelerator (B) is within this range, an appropriate vulcanization speed can be obtained, and the insufficiency of the crosslinked structure due to insufficient vulcanization treatment is unlikely to occur, and scorching is unlikely to occur. In addition, the vulcanization density of the molded product obtained from the chloroprene copolymer latex composition according to this embodiment is also appropriate, so that the mechanical properties of the molded product are in an appropriate range by setting the amount of the vulcanization accelerator (B) within the above range.
[0045] The type of metal oxide (C) is not particularly limited, and for example, zinc oxide, lead oxide, and trilead tetroxide can be used, with zinc oxide being particularly preferred. The metal oxide (C) may be used alone or in combination of two or more kinds.
[0046] The amount of the metal oxide (C) contained in the chloroprene copolymer latex composition according to this embodiment is preferably 0.1 to 20.0 parts by mass, more preferably 0.25 to 15.0 parts by mass, and even more preferably 0.4 to 10.0 parts by mass, based on 100 parts by mass of the solid content in the latex of the chloroprene copolymer (A). If the amount of the metal oxide (C) is 0.1 parts by mass or more, a suitable vulcanization rate is obtained, which is preferable. If the amount of the metal oxide (C) is 20.0 parts by mass or less, a good crosslinked structure is obtained by the vulcanization treatment, and scorching is unlikely to occur. In addition, the colloidal state of the chloroprene copolymer latex composition is stabilized, which is preferable because problems such as precipitation are unlikely to occur.
[0047] The type of sulfur (D) is not particularly limited, and in addition to powdered sulfur, precipitated sulfur, colloidal sulfur, surface-treated sulfur, and insoluble sulfur, sulfur-containing compounds such as polysulfides and polymeric polysulfides (excluding the above vulcanization accelerators) can be used. The sulfur (D) may be used alone or in combination of two or more. The amount of sulfur (D) contained in the chloroprene copolymer latex composition according to this embodiment is preferably 0.1 to 10.0 parts by mass, more preferably 0.2 to 7.0 parts by mass, and even more preferably 0.8 to 5.0 parts by mass, based on 100 parts by mass of the solid content in the latex of the chloroprene copolymer (A). If the amount of sulfur (D) is within this range, an appropriate vulcanization rate can be obtained, and insufficient crosslinking structure due to insufficient vulcanization treatment is unlikely to occur, and scorching is unlikely to occur, which is preferable. In addition, the colloidal state of the chloroprene copolymer latex composition is stabilized, so that problems such as sedimentation are unlikely to occur, which is preferable.
[0048] The type of antioxidant (E) is not particularly limited, but when it is desired that the molded product has high heat resistance, it is preferable to use an antioxidant that prevents aging due to heat in combination with an antioxidant that prevents aging due to ozone.
[0049] Examples of antioxidants that prevent aging due to heat include diphenylamine-based antioxidants such as octylated diphenylamine, p-(p-toluene-sulfonylamido)diphenylamine, 4,4'-bis(α,α-dimethylbenzyl)diphenylamine, etc. When such antioxidants are added, the molded product tends to have heat resistance and also stain resistance (such as discoloration prevention).
[0050] Examples of antioxidants that prevent ozone aging include N,N'-diphenyl-p-phenylenediamine (DPPD) and N-isopropyl-N'-phenyl-p-phenylenediamine (IPPD).
[0051] When the chloroprene copolymer rubber molded product according to the present embodiment is used as a disposable medical glove, importance is attached to the appearance (particularly color tone) and hygiene, so it is preferable to use a hindered phenol-based antioxidant as the antioxidant (E). Examples of the hindered phenol-based antioxidant include 2,2'-methylenebis-(4-ethyl-6-t-butylphenol) and 4,4'-methylenebis-(2,6-di-t-butylphenol).
[0052] The amount of the antioxidant (E) contained in the chloroprene copolymer latex composition according to the present embodiment is preferably 0.1 to 10.0 parts by mass, more preferably 0.5 to 5.5 parts by mass, and even more preferably 1.0 to 4.8 parts by mass, based on 100 parts by mass of the solid content in the latex of the chloroprene copolymer (A). When the amount of the antioxidant (E) is within this range, a sufficient antioxidant effect is obtained, the vulcanization treatment is not inhibited, and deterioration of color tone is unlikely to occur.
[0053] The chloroprene copolymer latex composition may contain a synthetic rubber (F) that is mixable with the latex of the chloroprene copolymer (A). If the chloroprene copolymer latex composition contains a synthetic rubber (F), it is preferable that the molded product can be given the properties of another rubber that the chloroprene copolymer (A) does not have. The mixable synthetic rubber (F) is not particularly limited, and may be selected from isoprene rubber, chloroprene rubber (excluding the chloroprene copolymer (A)), acrylonitrile-butadiene rubber, butadiene rubber, and the like. In terms of compatibility with the chloroprene copolymer (A), isoprene rubber or chloroprene rubber (excluding the chloroprene copolymer (A)) is more preferable. If necessary, two or more synthetic rubbers (F) may be used in the chloroprene copolymer latex composition.
[0054] The synthetic rubber (F) in the chloroprene copolymer latex composition may be blended within a range that does not impair the object of the present invention. When the chloroprene copolymer latex composition contains a mixable synthetic rubber (F), the proportion (upper limit) of the synthetic rubber (F) is preferably 25% by mass or less, more preferably 10% by mass or less, when the total of the solid content of the latex of the chloroprene copolymer (A) and the synthetic rubber (F) is taken as 100% by mass. The proportion (lower limit) of the synthetic rubber (F) is preferably 1% by mass or more, more preferably 3% by mass or more, and even more preferably 5% by mass or more. If the proportion of the synthetic rubber (F) is 25% by mass or less, the maturation time and / or vulcanization time of the chloroprene copolymer latex composition is short, which is preferable. If the proportion of the synthetic rubber (F) is 10% by mass or more, it is preferable in terms of expressing the characteristics of the other synthetic rubber (F). The amount of the synthetic rubber (F) in the chloroprene copolymer latex composition is preferably 33 parts by mass or less, more preferably 11 parts by mass or less, based on 100 parts by mass of the chloroprene copolymer (A). The amount of the synthetic rubber (F) in the chloroprene copolymer latex composition is preferably 1 part by mass or more, more preferably 3.1 parts by mass or more, and even more preferably 5.3 parts by mass or more, based on 100 parts by mass of the chloroprene copolymer (A).
[0055] When the chloroprene copolymer latex composition contains the chloroprene copolymer (A) and the synthetic rubber (F), the chloroprene copolymer latex composition may contain 0.1 to 10.0 parts by mass of the vulcanization accelerator (B), 0.1 to 20.0 parts by mass of the metal oxide (C), 0.1 to 10.0 parts by mass of the sulfur (D), and 0.1 to 10.0 parts by mass of the antioxidant (E), provided that the total of the solid content of the latex of the chloroprene copolymer (A) and the synthetic rubber (F) is 100 parts by mass. The synthetic rubber (F) may be a latex in which fine particles of the synthetic rubber (F) are dispersed. When the latex of the synthetic rubber (F) is used, the chloroprene copolymer latex composition may contain 0.1 to 10.0 parts by mass of the vulcanization accelerator (B), 0.1 to 20.0 parts by mass of the metal oxide (C), 0.1 to 10.0 parts by mass of the sulfur (D), and 0.1 to 10.0 parts by mass of the antioxidant (E), assuming that the total of the solid content of the latex of the chloroprene copolymer (A) and the solid content of the latex of the synthetic rubber (F) is 100 parts by mass.
[0056] In addition to the chloroprene copolymer (A), the vulcanization accelerator (B), the metal oxide (C), the sulfur (D), the antioxidant (E), and the synthetic rubber (F), other additives may be added to the chloroprene copolymer latex composition according to the present embodiment as desired, so long as the object of the present invention is not impaired. Examples of additives that can be added include a pH adjuster, a filler, a pigment, a colorant, an antifoaming agent, and a thickener.
[0057] [Chloroprene copolymer rubber moldings] The chloroprene copolymer latex composition according to the present invention can be molded and cured to obtain a chloroprene copolymer rubber molded product. For example, the chloroprene copolymer latex composition can be molded by a dipping process to obtain a dipping product. Before the immersion process, the chloroprene copolymer latex composition may be aged under a predetermined condition. The aging temperature is 15 to 40° C., and the aging time is 15 to 72 hours. For example, aging at 23° C. for 20 hours may be used. The aging starts when the latex of the chloroprene copolymer (A) is mixed with all of the vulcanization accelerator (B), the metal oxide (C), the sulfur (D), and the antioxidant (E). After aging the chloroprene copolymer latex composition, it is immersed and coagulated. , dry A film-like molded product is obtained by carrying out the steps of drying and vulcanization (curing) in this order.
[0058] The immersion and coagulation treatment can be carried out by submerging a plate or mold coated with a coagulant in the chloroprene copolymer latex composition for a predetermined period of time, and depositing the solids in the chloroprene copolymer latex composition, such as chloroprene copolymer (A), on the surface of the plate or mold. This is presumably because, in the chloroprene copolymer latex composition, fine particles covered with a film of an emulsifier having surface activity are formed, and the film of the fine particles is destroyed by the action of the coagulant attached to the surface of the plate or mold, causing the chloroprene copolymer (A) and the like in the fine particles to adhere to the surface of the plate or mold. A metal salt, for example a metal nitrate, can be used as the coagulant. In order to avoid appearance problems of the molded product, such as the formation of blisters and pinholes, a drying step (rough drying step) may be carried out at a relatively low temperature of 70°C to 100°C before the vulcanization step.
[0059] The vulcanization temperature in the vulcanization step can be 110 to 130° C. For example, the solid content of the chloroprene copolymer latex composition deposited by the immersion and coagulation treatment can be vulcanized in air at 110° C. The vulcanization time in the above vulcanization temperature range can be, for example, 20 minutes or more and 90 minutes or less, but it is preferable to perform the vulcanization sufficiently within a range in which the tensile strength and tensile elongation of the molded product are not deteriorated.
[0060] The composition deposited on the surface of the plate or mold is vulcanized under the above conditions to obtain a chloroprene copolymer rubber molded product. The chloroprene copolymer rubber molded product preferably has a 500% elastic modulus of 0.5 to 1.6 MPa, a tensile strength of 19 to 30 MPa, and a tensile elongation of 800 to 1500%. The chloroprene copolymer rubber molded product according to this embodiment has excellent flexibility and a tensile strength within a desired range.
[0061] [Disposable medical gloves] The chloroprene copolymer rubber molded product can be suitably used, particularly, as disposable medical gloves. If the 100% elastic modulus of the chloroprene copolymer rubber molded product is 0.60 MPa or less, flexibility is obtained in the medical disposable gloves, which is preferable. The lower limit of the 100% elastic modulus of the chloroprene copolymer rubber molded product may be, for example, 0.40 MPa or more. If the 500% elastic modulus of the chloroprene copolymer rubber molded product is 0.5 to 1.6 MPa, the disposable medical gloves have a soft feel, so that the user does not get tired even when wearing them for a long time. If the 500% elastic modulus of the chloroprene copolymer rubber molded product is 1.6 MPa or less, the force of the fingers of the disposable medical gloves to return to their original shape when bent is appropriate, which is preferable. If the tensile strength of the chloroprene copolymer rubber molded product is 19 MPa or more, sufficient strength is obtained as a disposable medical glove, and breakage is unlikely to occur, which is preferable. The upper limit of the tensile strength of the chloroprene copolymer rubber molded product may be, for example, 30 MPa or less. If the tensile elongation of the chloroprene copolymer rubber molded product is 800% or more, the disposable medical gloves are less likely to break, which is preferable. The upper limit of the tensile elongation of the chloroprene copolymer rubber molded product may be, for example, 1500% or less.
[0062] When the chloroprene copolymer rubber molded product is used as a dipping product, a powder such as calcium carbonate or cornstarch may be applied to the surface of the dipping product in order to reduce friction between the dipping product and an object with which the dipping product comes into contact. Here, the object may be an object with which the dipping product comes into contact, or a part of the body of a user who uses or puts on the dipping product. When the object is a part of the user's body, the friction between the dipping product and the object can be reduced by applying a powder to the surface of the dipping product, and as a result, the usability and ease of putting on and taking off the dipping product can be improved. However, since powder is thought to cause allergies and infections, it is preferable not to use powder on the surface of the dipping product (no powder).
[0063] The molded product may be a multi-layered dipping product having a multi-layered structure in which a layer of the chloroprene copolymer rubber molded product and a layer of a polymer other than the layer of the chloroprene copolymer rubber molded product are laminated. In this case, the layer of the chloroprene copolymer rubber molded product is at least one layer of the multi-layered structure. Examples of polymers that can be used for layers other than the layer of the chloroprene copolymer rubber molded product among the layers forming the multi-layered structure include isoprene homopolymer polymer, chloroprene homopolymer polymer, acrylonitrile-butadiene polymer, butadiene polymer, polyvinyl chloride, polyethylene, etc. The molded product of the present invention may be used for any layer of the multi-layered structure, but when a polymer having a smaller friction with the object than the chloroprene copolymer rubber molded product is used for a layer in contact with the object, the friction between the multi-layered dipping product and the object is reduced compared to when a layer of the chloroprene copolymer rubber molded product is in contact with the object. For example, when the object is a part of the user's body, the multi-layer dipped product can be made easier to put on and take off by using a layer of a polymer that has lower friction with the surface of the user's body than the chloroprene copolymer rubber molded product as the layer in contact with the user's body. The multi-layer dipped product can be manufactured by a known manufacturing method. EXAMPLES
[0064] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0065] <Calculation method of polymerization conversion rate> The emulsion after the start of polymerization of chloroprene copolymer (A) was collected and dried by standing in an oven at 141°C for 30 minutes to obtain a dry product. The dry product obtained by the drying process contains polymer and solids other than polymer. Therefore, the mass of the solids other than polymer was calculated from the amount of polymerization raw materials charged, and the mass of the solids other than polymer was calculated from the mass of the dry product obtained by drying the emulsion after the start of polymerization minus the mass of the solids other than polymer. The polymerization conversion rate was calculated by formula (1) using the value obtained by subtracting the mass of the solids other than polymer from the mass of the dry product obtained by drying the emulsion after the start of polymerization as the "production amount of chloroprene copolymer (A)". Polymerization conversion rate (mass%) = [(amount of chloroprene copolymer (A) produced) / (mass of all monomers charged)] × 100 (1) The "feed mass of all monomers" in formula (1) is the sum of the feed amount of 2-chloro-1,3-butadiene (A-1), the feed amount of 2-methyl-1,3-butadiene (A-2), and the feed amount of any monomer (A-3) contained in the amount of emulsion collected to obtain a dry product.
[0066] [Method of measuring physical properties of chloroprene copolymer (A) latex] As described later, after the polymerization of the chloroprene copolymer (A) is terminated, the unreacted 2-chloro-1,3-butadiene (A-1), 2-methyl-1,3-butadiene (A-2), and optional monomer (A-3) are removed to obtain a latex of the chloroprene copolymer (A). Various physical properties of the obtained latex of the chloroprene copolymer (A) were evaluated by the following methods.
[0067] <How to calculate solid content> The latex of the chloroprene copolymer (A) was sampled, and the mass of the sampled latex of the chloroprene copolymer (A) was weighed. The weighed latex of the chloroprene copolymer (A) was then dried by standing in an oven at 141°C for 30 minutes to obtain a dry product. The solid content of the latex of the chloroprene copolymer (A) was calculated from the mass of the latex of the chloroprene copolymer (A) before drying and the mass of the obtained dry product using formula (2). Solid content (mass%) = [(mass of dried product) / (mass of collected chloroprene copolymer (A) latex)] × 100 (2)
[0068] <Ratio of tetrahydrofuran insoluble matter in chloroprene copolymer (A)> The tetrahydrofuran insoluble content of the chloroprene copolymer (A) was measured as follows. That is, 1 g of the latex of the chloroprene copolymer (A) was dropped into 100 mL of tetrahydrofuran at 25°C, and the mixture was shaken for 10 hours using a shaker (SA300) manufactured by Yamato Scientific Co., Ltd. After the shaking treatment, the mixture of the latex of the chloroprene copolymer (A) and tetrahydrofuran was centrifuged using a centrifugal separator (H-9R manufactured by Kokusan Co., Ltd.) to obtain a supernatant dissolved phase. The obtained dissolved phase was heated to 100°C, tetrahydrofuran was evaporated over 1 hour, and the mass of the dried product was measured. This gives the mass of the soluble portion of the chloroprene copolymer (A) that was dissolved in the dissolved phase.
[0069] The mass of the chloroprene copolymer (A) in 1 g of the latex of the chloroprene copolymer (A) and the mass of the soluble matter described above were substituted into formula (3) to calculate the content of the tetrahydrofuran-insoluble matter that does not dissolve in tetrahydrofuran at 25°C (tetrahydrofuran insoluble matter rate) in the chloroprene copolymer (A). Tetrahydrofuran insoluble content (mass%) = {1-[(mass of dissolved portion) / (mass of chloroprene copolymer (A) in 1 g of chloroprene copolymer (A) latex)]} × 100 (3) In the formula (3), the mass of the chloroprene copolymer (A) in 1 g of the latex of the chloroprene copolymer (A) was regarded as the mass of the solid content obtained by drying 1 g of the latex of the chloroprene copolymer (A). When the latex of the chloroprene copolymer (A) was dried, it was dried by leaving it in an oven at 141°C for 30 minutes.
[0070] <Weight average molecular weight (Mw)> Hereinafter, an example of how to determine the weight average molecular weight (Mw) of the tetrahydrofuran soluble content in the chloroprene copolymer (A) at 25°C will be described. The supernatant soluble phase after centrifugal sedimentation was prepared and separated by the same treatment as in the preparation of the sample for measuring the tetrahydrofuran insoluble content, and the sample was prepared by diluting with tetrahydrofuran. The molecular weight of the obtained sample was measured in terms of polystyrene by GPC (gel permeation chromatography) to measure the weight average molecular weight (Mw).
[0071] The GPC measurement conditions were as follows: GPC measurement device was LC-20AD manufactured by Shimadzu Corporation; detector was RID-10A (differential refractive index detector) manufactured by Shimadzu Corporation; column type was PLgel 10 μm MiniMIX-B manufactured by Agilent Technologies, Inc.; eluent was tetrahydrofuran (manufactured by Kanto Chemical Co., Ltd., for HPLC); column temperature: 40°C; and flow rate: 0.4 ml / min.
[0072] <Monomer unit content in chloroprene copolymer (A)> The content of the component derived from 2-methyl-1,3-butadiene (A-2) in the chloroprene copolymer (A) is 1 The chloroprene copolymer (A) latex was coagulated with methanol and dried, and then deuterated chloroform was added to the coagulated product. After filtering out the material insoluble in deuterated chloroform, the resulting solution was 1 H-NMR analysis was performed. 1 For the H-NMR analysis, a JNM-AL400 manufactured by JEOL Ltd. was used as a measuring device, and tetramethylsilane was used as the standard for chemical shifts. 1 The content of the component derived from 2-methyl-1,3-butadiene (A-2) was calculated according to formula (4) from the peak (5.4 ppm) derived from 2-chloro-1,3-butadiene (A-1) and the peak (5.1 ppm) derived from 2-methyl-1,3-butadiene (A-2) in the H-NMR spectrum. Content of 2-methyl-1,3-butadiene (A-2) derived components (mol%) = (peak area at 5.1 ppm) / (peak area at 5.1 ppm + peak area at 5.4 ppm) × 100 (4)
[0073] Even when the chloroprene copolymer (A) contains monomer units derived from the monomer (A-3), if the monomer (A-3) does not have a peak overlapping with the peaks at 5.1 ppm and 5.4 ppm, formula (4) can be used to calculate the proportion of 2-methyl-1,3-butadiene (A-2) in the total of 2-chloro-1,3-butadiene (A-1) and 2-methyl-1,3-butadiene (A-2). When determining the content ratio of monomer (A-3), the ratio of monomer (A-3) to the total of 2-chloro-1,3-butadiene (A-1) and monomer (A-3) is calculated from the same formula as formula (4) using the peak area of the peak derived from monomer (A-3) that does not overlap with the peaks of 2-chloro-1,3-butadiene (A-1) and 2-methyl-1,3-butadiene (A-2). Similarly, the ratio of monomer (A-3) when the total of monomer units derived from 2-chloro-1,3-butadiene (A-1) and monomer units derived from 2-methyl-1,3-butadiene (A-2) is 100 mol parts can also be obtained.
[0074] When monomer (A-3) has a peak overlapping with the peak at 5.1 ppm and the peak at 5.4 ppm, 1 H- 1 Using the results of multidimensional NMR measurements such as H COSY (COrrelation SpectroscopY), the peaks originating from 2-chloro-1,3-butadiene (A-1), 2-methyl-1,3-butadiene (A-2), and the monomer (A-3) are identified, and the proportions of each substance are determined by performing a similar calculation using the peak areas.
[0075] [Example 1] (1) Preparation of latex of chloroprene copolymer (A) In a 5 L reaction vessel, 1200 g of 2-chloro-1,3-butadiene (A-1), 300 g of 2-methyl-1,3-butadiene (A-2), 1290 g of pure water, 65 g of disproportionated rosin acid (R-600, manufactured by Arakawa Chemical Industries, Ltd.), 17.1 g of potassium hydroxide, 3.9 g of sodium hydroxide, 3.3 g of sodium salt of β-naphthalenesulfonic acid formalin condensate, and 1.65 g of n-dodecyl mercaptan were charged. The starting materials charged in the reaction vessel were emulsified, and the rosin acid was converted into rosin acid soap.
[0076] 2-Chloro-1,3-butadiene (A-1) and 2-methyl-1,3-butadiene (A-2) were mixed as raw monomers, and pure water was mixed as a dispersion medium for emulsion polymerization. Disproportionated rosin acid, potassium hydroxide, and sodium hydroxide were mixed as raw materials for the emulsifier, and the sodium salt of β-naphthalenesulfonic acid formalin condensate was mixed as an emulsifier.
[0077] To the emulsion obtained by emulsifying the starting materials, 4 g of potassium persulfate was added as a polymerization initiator, and emulsion polymerization was carried out at 30°C under a nitrogen gas atmosphere, and the polymerization was stopped when the polymerization conversion rate of all monomers reached 84% by mass (after 6.1 hours). The polymerization conversion rate was calculated as described above. Subsequently, the unreacted 2-chloro-1,3-butadiene (A-1) and 2-methyl-1,3-butadiene (A-2) were removed by steam distillation to obtain a latex of chloroprene copolymer (A1). The physical properties of the latex of chloroprene copolymer (A1) were as follows. Solid content: 45% by mass Tetrahydrofuran insoluble content: 2% by mass Weight average molecular weight (Mw) of chloroprene copolymer (A1) soluble in tetrahydrofuran at 25°C: 600,000 Proportion of monomer units derived from 2-methyl-1,3-butadiene (A-2) in chloroprene copolymer (A1): 15 mol%
[0078] (2) Preparation of chloroprene copolymer latex composition The latex of the chloroprene copolymer (A1) obtained in the above (1) was charged in a vessel equipped with a stirrer together with the vulcanization accelerator (B), the metal oxide (C), the sulfur (D), and the antioxidant (E). The charged amounts of the vulcanization accelerator (B) were 0.5 parts by mass of 2-mercaptobenzothiazole zinc (Noccela (registered trademark) MZ manufactured by Ouchi Shinko Chemical Industry Co., Ltd.), 0.5 parts by mass of zinc dibutyldithiocarbamate (Noccela (registered trademark) BZ manufactured by Ouchi Shinko Chemical Industry Co., Ltd.), and 1.0 part by mass of sodium dibutyldithiocarbamate (Noccela (registered trademark) TP manufactured by Ouchi Shinko Chemical Industry Co., Ltd.) relative to 100 parts by mass of the solid content in the latex of the chloroprene copolymer (A1). The amounts of the metal oxide (C), sulfur (D), and antioxidant (E) charged were 0.5 parts by mass of zinc oxide (AZ-SW manufactured by Osaki Kogyo Co., Ltd.), 1.5 parts by mass of sulfur (S-50 manufactured by Nippon Color Kogyo Co., Ltd.), and 2.0 parts by mass of a phenol-based antioxidant (K-840 manufactured by Chukyo Yushi Co., Ltd.) relative to 100 parts by mass of the solid content in the latex of the chloroprene copolymer (A1). The mixture charged in a container equipped with a stirrer was stirred for 20 minutes to mix uniformly, thereby obtaining a chloroprene copolymer latex composition. After stirring, the chloroprene copolymer latex composition was left to stand at 23°C for 20 hours to mature.
[0079] In addition, since zinc oxide AZ-SW, sulfur S-50, and phenol-based antioxidant K-840 are in the form of a dispersion in which the active ingredients zinc oxide, sulfur (D), and antioxidant (E) are dispersed in a liquid medium, the amounts of zinc oxide AZ-SW, sulfur S-50, and phenol-based antioxidant K-840 mentioned above are the amounts of only the active ingredients of zinc oxide AZ-SW, sulfur S-50, and K-840 charged.
[0080] (3) Film preparation The chloroprene copolymer latex composition obtained in (2) above was used to obtain a chloroprene copolymer rubber molded product (film) by a dipping processing method. A ceramic plate measuring 200 mm in length, 100 mm in width, and 5 mm in thickness was prepared as a mold for the film. This mold was immersed in a 30% by mass aqueous solution of calcium nitrate, then removed and dried in an oven at 40° C. for 10 minutes to allow calcium nitrate, which acts as a coagulant, to adhere to the surface of the mold.
[0081] The dried mold was then immersed in the chloroprene copolymer latex composition obtained in (2) above, and the solid content of the chloroprene copolymer latex composition was deposited on the surface of the mold. The mold was then removed from the chloroprene copolymer latex composition and dried in an oven at 70°C for 30 minutes. Next, the mold with the solids deposited on the surface was heated in an oven at 110°C for 90 minutes to vulcanize and harden the solids of the chloroprene copolymer latex composition deposited on the surface of the mold. After cooling in the air, the surface-hardened molded product of the mold was cut into a desired shape and size to obtain a film as a molded product of the vulcanized chloroprene copolymer rubber.
[0082] [Thermal degradation treatment of molded products and measurement method of physical properties of molded products] The film was cut into test pieces using a No. 6 dumbbell as specified in JIS K6251-2017. The thickness of the test pieces was 0.15 to 0.25 mm.
[0083] <Tensile strength, tensile elongation, elastic modulus> A tensile test was carried out at 23°C according to JIS K6251-2017 to measure the tensile strength, tensile elongation, elastic modulus at 100% elongation (100% elastic modulus), and elastic modulus at 500% elongation (500% elastic modulus). The various physical properties of the film measured as described above are summarized in Table 1.
[0084] [Example 2] A chloroprene copolymer latex composition was prepared in the same manner as in Example 1, except that the vulcanization accelerator (B), zinc dibutyldithiocarbamate (Noccela (registered trademark) BZ manufactured by Ouchi Shinko Chemical Industry Co., Ltd.) was changed to zinc diethylthiocarbamate (Noccela (registered trademark) EZ manufactured by Ouchi Shinko Chemical Industry Co., Ltd.), and the film and test piece were subjected to various evaluations in the same manner as in Example 1. The results are shown in Table 1.
[0085] [Example 3] A chloroprene copolymer latex composition, a film, and a test piece were prepared in the same manner as in Example 1, except that the amount of zinc oxide was changed to 5.0 parts by mass and the vulcanization time was changed to 20 minutes, and various evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.
[0086] [Comparative Example 1] A chloroprene copolymer latex composition, a film, and a test piece were prepared in the same manner as in Example 1, except that only 1.0 part by mass of 2-mercaptobenzothiazole zinc (Noccela (registered trademark) MZ manufactured by Ouchi Shinko Chemical Industry Co., Ltd.) was used as the vulcanization accelerator (B) and the vulcanization time was set to 20 minutes, and various evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.
[0087] [Comparative Example 2] A chloroprene copolymer latex composition, a film, and a test piece were prepared in the same manner as in Example 1, except that only 1.0 part by mass of zinc dibutyldithiocarbamate (Noccela (registered trademark) BZ manufactured by Ouchi Shinko Chemical Industry Co., Ltd.) was used as the vulcanization accelerator (B) and the vulcanization time was set to 20 minutes, and various evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.
[0088] [Comparative Example 3] A chloroprene copolymer latex composition, a film, and a test piece were prepared in the same manner as in Example 1, except that only 1.0 part by mass of diphenyl guanidine (Noccela (registered trademark) D manufactured by Ouchi Shinko Chemical Industry Co., Ltd.) was used as the vulcanization accelerator (B) and the vulcanization time was set to 20 minutes, and various evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.
[0089] [Comparative Example 4] As the vulcanization accelerator (B), 1.0 part by mass of diphenyl guanidine (Noccela (registered trademark) D manufactured by Ouchi Shinko Chemical Industry Co., Ltd.) and N,N'-diphenyl guanidine were used. centre A chloroprene copolymer latex composition, a film, and a test piece were prepared in the same manner as in Example 1, except that 1.0 part of phenylthiourea (Noccela (registered trademark) C manufactured by Ouchi Shinko Chemical Industry Co., Ltd.) was used and the vulcanization time was changed to 20 minutes, and various evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.
[0090] [Comparative Example 5] A chloroprene copolymer latex composition, a film, and a test piece were prepared in the same manner as in Example 1, except that the monomer charged in the reaction vessel when preparing the chloroprene copolymer latex was 1500 g of 2-chloro-1,3-butadiene (A-1) and 2-methyl-1,3-butadiene (A-2) was not used, and various evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.
[0091] [Comparative Example 6] Among the vulcanization accelerators (B) used in Example 1, 1.0 part by mass of sodium dibutyldithiocarbamate (Noccela (registered trademark) TP manufactured by Ouchi Shinko Chemical Industry Co., Ltd.) was changed to 0.25 part by mass of diphenyl guanidine (Noccela (registered trademark) D manufactured by Ouchi Shinko Chemical Industry Co., Ltd.) and the vulcanization time was changed to 20 minutes. In the same manner as in Example 1, except for this, a chloroprene copolymer latex composition, a film and a test piece were prepared and various evaluations were performed in the same manner as in Examples. The results are shown in Table 1.
[0092] [Table 1]
[0093] In Examples 1 to 3, in which both a thiazole-based vulcanization accelerator and a carbamate-based vulcanization accelerator were used as the vulcanization accelerator (B) in the chloroprene copolymer latex composition, the films after vulcanization treatment showed high flexibility and strength. The flexibility and strength of the films obtained in Examples 1 to 3 are comparable to the results of Comparative Example 6, in which diphenyl guanidine capable of performing good vulcanization treatment was used. In other words, by using both a thiazole-based vulcanization accelerator and a carbamate-based vulcanization accelerator as the vulcanization accelerator (B), a molded product with desired flexibility and strength could be produced without using a vulcanization accelerator (diphenyl guanidine) for which skin sensitization is a concern. This result is considered to be due to the fact that when a thiazole-based vulcanization accelerator is used, a crosslinked structure is formed immediately after the vulcanization temperature is reached, and when a carbamate-based vulcanization accelerator is used, the formation of a crosslinked structure begins after a certain period of time has elapsed since the vulcanization temperature is reached. That is, it is considered that a crosslinked structure is formed by the thiazole vulcanization accelerator at the early stage of vulcanization treatment, and even if the thiazole vulcanization accelerator is deactivated, a crosslinked structure is formed by the carbamate vulcanization accelerator, so that the crosslinked structure is continuously formed during the vulcanization treatment. On the other hand, in Comparative Examples 1 and 2, in which either the thiazole-based vulcanization accelerator or the carbamate-based vulcanization accelerator was used alone, the film could not be peeled off from the mold after vulcanization, and the physical properties of the film after vulcanization could not be evaluated. This result is considered to be due to the fact that in Comparative Example 1, in which only the thiazole-based vulcanization accelerator was used, a crosslinked structure was formed only at the early stage of vulcanization, and in Comparative Example 2, in which only the carbamate-based vulcanization accelerator was used, a crosslinked structure was formed only after the carbamate-based vulcanization accelerator was activated. In Comparative Example 3, in which a guanidine-based vulcanization accelerator was used alone as a vulcanization accelerator, the physical properties of the film after vulcanization treatment could not be evaluated. The tensile strength of the molded product obtained in Comparative Example 4, in which a guanidine-based vulcanization accelerator and a thiourea-based vulcanization accelerator were used in combination, was insufficient for use as a surgical glove. In Comparative Example 5, in which the monomer unit of the chloroprene copolymer was only 2-chloro-1,3-butadiene (A-1), the physical properties of the film after vulcanization treatment could not be evaluated.
Claims
1. A chloroprene copolymer latex composition comprising a chloroprene copolymer (A) and a vulcanization accelerator (B), The chloroprene copolymer (A) is a chloroprene copolymer containing chloroprene and a monomer unit derived from 2-methyl-1,3-butadiene, The chloroprene copolymer latex composition, wherein the vulcanization accelerator (B) contains a carbamate-based vulcanization accelerator and a thiazole-based vulcanization accelerator.
2. 2. The chloroprene copolymer latex composition according to claim 1, wherein the thiazole vulcanization accelerator is zinc 2-mercaptobenzothiazole.
3. 3. The chloroprene copolymer latex composition according to claim 1, wherein the carbamate-based vulcanization accelerator is at least one selected from the group consisting of zinc diethyldithiocarbamate, zinc dibutyldithiocarbamate, and sodium dibutyldithiocarbamate.
4. The chloroprene copolymer latex composition according to any one of claims 1 to 3, further comprising a metal oxide (C), sulfur (D), and an antioxidant (E).
5. The chloroprene copolymer (A) and the optional synthetic rubber (F) are mixed in a total amount of 100 parts by mass, 1.0 to 10.0 parts by mass of a vulcanization accelerator (B), 0.1 to 20.0 parts by mass of a metal oxide (C), 0.1 to 10.0 parts by mass of sulfur (D), and 0.1 to 10.0 parts by mass of antioxidant (E) The chloroprene copolymer latex composition of claim 4 , comprising
6. Contains synthetic rubber (F), The chloroprene copolymer latex composition according to claim 5, wherein a ratio of the synthetic rubber (F) is 1 to 33 mass% when a total of the chloroprene copolymer (A) and the synthetic rubber (F) is 100 mass%.
7. A chloroprene copolymer rubber molded product obtained by curing the chloroprene copolymer latex composition according to any one of claims 1 to 6.
8. A dipped product, which is produced by molding the chloroprene copolymer latex composition according to any one of claims 1 to 6 by a dipping method and curing the same.
9. 9. The dipped product of claim 8 which is a glove.
10. 10. The dipped product of claim 9 which is a disposable medical glove.
11. The dipped product according to any one of claims 8 to 10, wherein the surface of the dipped product is free of powder that reduces friction between the dipped product and an object with which the dipped product comes into contact.
12. 7. A multi-layer dipping product having a multi-layer structure in which a layer of a chloroprene copolymer rubber molded product obtained by curing the chloroprene copolymer latex composition according to any one of claims 1 to 6 and a layer other than the layer are laminated.
Citation Information
Patent Citations
Method for manufacturing chloroprene polymer and composition thereof
JP2003055409A
Foamed elastomer and method for producing the same
JP2008056858A
Vibration-proofing rubber material and automotive engine mount using the same
JP2009185136A
Chloroprene copolymer latex composition and its compact
JP2019044116A
Chloroprene polymer latex and manufacturing method therefor
JP2019143002A